2011
DOI: 10.14236/jhi.v19i3.808
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted history-taking systems (CAHTS) in health care: benefits, risks and potential for further development

Abstract: Background A computer-assisted history-taking system (CAHTS) is a tool that aids clinicians in gathering data from patients to inform a diagnosis or treatment plan. Despite the many possible applications and even though CAHTS have been available for nearly three decades, these remain underused in routine clinical practice. Objective Through an interpretative review of the literature, we provide an overview of the field of CAHTS, which also offers an understanding of the impact of these systems on policy, pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…Our findings are consistent with other reviews on the use of computer-assisted history taking systems (CAHTS) for diabetes such as Pappas et al (2011) which found that CAHTS can save professionals' time, improve delivery of care to those with special needs and also facilitate the collection of information, especially potentially sensitive information (e.g. sexual history, alcohol consumption).…”
Section: Cahts For Cvd Managementsupporting
confidence: 91%
“…Our findings are consistent with other reviews on the use of computer-assisted history taking systems (CAHTS) for diabetes such as Pappas et al (2011) which found that CAHTS can save professionals' time, improve delivery of care to those with special needs and also facilitate the collection of information, especially potentially sensitive information (e.g. sexual history, alcohol consumption).…”
Section: Cahts For Cvd Managementsupporting
confidence: 91%
“…The use of CAHTS has the potential to improve quality and comprehensiveness of information captured, reduce data entry errors, save time and facilitate acquisition of sensitive patient information [24]. It can be used from the convenience of home, while travelling, or while in the waiting room.…”
Section: The Patient’s Medicines Management Journeymentioning
confidence: 99%
“…This patient-administered sexual history taking can be computer or paper-based [7578]. The use of a computerised tool to elicit patients’ sexual histories has the advantages of saving physicians’ time, of being acceptable to both patients and physicians, of improving care for patients’ specific needs by patient screening and routing, and of improving information collection, especially sensitive information [74, 79, 80]. While high literacy rates [96.1% among males and 92% among females] and a rapid increase in computer/Internet usage in Vietnam [0.3% in 2000 to 34% in 2012] [81] may suggest that ACASI could be feasible for sexual history taking in Vietnam, further research in this area is necessary to evaluate the practicality of using this approach in a country like Vietnam, and whether patients and health professionals would access information on sexual health via e-technology.…”
Section: Discussionmentioning
confidence: 99%